36. ONLINE LEARNING EXPERIENCE DỦRING THE 2021-2022 ACADEMIC YEAR OF 5th YEAR STUDENTS (COURSE 2018-2024) OF MEDICAL DOCTOR PROGRAM, HANOI MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2025)
Background: Describe the online learning experience in the 2021-2022 academic year of 5th year students (course 2018-2024) of the Medical Doctor program, Hanoi Medical University.Methods: A cross-sectional descriptive study was conducted on 272 5th year medical students (2018-2024) using a self-administered questionnaire.Results: 92,9% of students studied theory, and 78,7% participated in clinical practice online. The modules and lessons were designed in a clear and precise way (66,2%); The lecturer used active teaching methods that stimulated brainstorming (69,4%), however only 50,7% of students boldly express their opinions in class. During online lectures, students were able to freely discuss with their peers in separate Zoom rooms (75,7%). During clinical practice, since the lessons were operated via video, students were not able to practice their examination skills directly on the patients (80,5%). During the learning process, students were interested in and enjoyed online learning (47,8%), and were able to experience new learning methods during the pandemic (78,6%). Advantages and disadvantages: Online learning saved time and travel costs, and students could save and review lectures (87,9%); it also reduced the risk of COVID-19 infection during the pandemic (90,8%). However, difficulty concentrating (43.4%), students could not fully experience the hospital environment and context as in real-life settings (57,3%), and there were limitations in practicing thinking skills and skills/gaining hands-on clinical experience (62,9%).Conclusion: Students had diverse experiences with online learning in various aspects, including teaching activities, interaction with lecturers, other students, patients, and the overall learning process. Online learning had many advantages but also posed challenges, particularly in clinical practice. To improve its effectiveness, it is necessary to select appropriate learning content and combine online learning with in-person instruction.
Keywords: Experience; Online learning; Medical student